Regulation of Autophosphorylation of Escherichia coli Nitrogen Regulator II by the PII Signal Transduction Protein - Jiang, Peng (American Society for Microbiology, 1999)
The nitrogen regulator II (NRII or NtrB)-NRI (NtrC) two-component signal transduction system regulates the transcription of nitrogen-regulated genes in Escherichia coli. The NRII protein has both kinase and phosphatase activities and catalyzes the phosphorylation and dephosphorylation of NRI, which activates transcription when phosphorylated. The phosphatase activity of NRII is activated by the PII signal transduction protein. We showed that PII was also an inhibitor of the kinase activity of NRII. The data were consistent with the hypothesis that the kinase and phosphatase activities of two-component system kinase/phosphatase proteins are coordinately and reciprocally regulated. The ability of PII to regulate NRII is allosterically controlled by the small-molecule effector 2-ketoglutarate, which binds to PII. We studied the effect of 2-ketoglutarate on the regulation of the kinase and phosphatase activities of NRII by PII, using a coupled enzyme system to measure the rate of cleavage of ATP by NRII. The data were consistent with the following hypothesis: when not complexed with 2-ketoglutarate, PII cannot bind to NRII and has no effect on its competing NRI kinase and phosphatase activities. Under these conditions, the kinase activity of NRII is dominant. At low 2-ketoglutarate concentrations, PII trimers complexed with a single molecule of 2-ketoglutarate interact with NRII to inhibit its kinase activity and activate its phosphatase activity. However, at high 2-ketoglutarate concentrations, PII binds additional ligand molecules and is rendered incapable of binding to NRII, thereby releasing inhibition of NRII’s kinase activity and effectively inhibiting its phosphatase activity (by failing to stimulate it).